1985
DOI: 10.2466/pms.1985.61.3.863
|View full text |Cite
|
Sign up to set email alerts
|

Signs of Neurobehavioral Dysfunction in a Sample of Learning Disabled Children: Stability and Concurrent Validity

Abstract: Of 270 learning disabled children with average intelligence and significant delays in reading comprehension a sample of 37 were evaluated for signs of neurobehavioral dysfunction. All such signs--primitive reflexes, equilibrium reactions, and postrotary nystagmus--were reliably assessed. A subsample of 19 children was compared with developmentally normal and mentally retarded samples for the occurrence of tonic neck reflexes and equilibrium reactions. The learning disabled children consistently showed devianci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
10
0
2
Order By: Relevance
“…dysleksji, której występowanie w przypadku braku integracji odru chów jest wnikliwie badane 15,16,20 , ale również braku uwa gi lub nadpobudliwości psychoruchowej. [17][18][19][21][22][23] Ustale nie jakościowej i ilościowej integracji odruchów u dzieci i wczesne wdrożenie terapii ma zatem ogromne znaczenie w ich dalszym rozwoju. Stwierdzenie u dzieci ryzyka zabu rzeń umożliwi niedopuszczenie do ich rozwinięcia się.…”
Section: Omówienieunclassified
“…dysleksji, której występowanie w przypadku braku integracji odru chów jest wnikliwie badane 15,16,20 , ale również braku uwa gi lub nadpobudliwości psychoruchowej. [17][18][19][21][22][23] Ustale nie jakościowej i ilościowej integracji odruchów u dzieci i wczesne wdrożenie terapii ma zatem ogromne znaczenie w ich dalszym rozwoju. Stwierdzenie u dzieci ryzyka zabu rzeń umożliwi niedopuszczenie do ich rozwinięcia się.…”
Section: Omówienieunclassified
“…We measured ATNR using the Schilder test 15. ATNR presents as the tonic reflex response that occurs in newborns; it normally vanishes at around 3 months of age.…”
Section: Methodsmentioning
confidence: 99%
“…22 Epidemiologically, the statistical equivalence between DDS and dyspraxia, and its comorbidity with DDS, is noteworthy. [5][6][7][10][11][12]22 Dyspraxia is a disorder of praxis, the Greek word meaning doing, acting, and practice. Praxis includes both knowing what to do and how to do it-doing something with ease and without effort.…”
Section: Developmental Delay Syndrome Linked To Motor Impairmentsmentioning
confidence: 99%
“…2 It has been shown that motor discoordination, especially affecting the postural and ocular muscles, is a common comorbid condition associated with this spectrum of disorders. [3][4][5][6][7] At this time, DDSs are thought to have multifactorial etiologies. 3,4,[8][9][10][11] The epidemiologic prevalence of these disturbances has been estimated to be as high as 5% to 20% (depending on a conservative definition).…”
mentioning
confidence: 99%